Differences in Chest X-Ray Imaging in Pulmonary Tuberculosis across Various Comorbidities - Subkhan, Mohammad; Rezacharawa, Meltritania Arief; Putra, Muslim Andala; Laitupa, Afrita Amalia; Permana, Putu Bagus Dharma; Irfana, Laily (MAGNA MEDIKA Berkala Ilmiah Kedokteran dan Kesehatan, 2024)
Background:  Tuberculosis (TB) remains a significant public health concern in Indonesia, with a high prevalence of cases, particularly in patients with comorbidities such as HIV infection, chronic obstructive pulmonary disease (COPD), diabetes mellitus (DM), and chronic kidney disease (CKD). Evidence suggested radiological variations in chest X-ray findings among these complex condition, which may pose significant challenges in accurately diagnosing pulmonary TB in clinical practice.Objective:  This study aimed to provide a comprehensive understanding of the variations in chest X-ray imaging in pulmonary TB patients with specific comorbidities, focusing on DM, CKD, and COPD.Methods: A cross-sectional study was conducted at Siti Khodijah Muhammadiyah Sepanjang Hospital by utilizing standardized medical records and chest X-ray results of 50 pulmonary patients with comorbidities.Results: The most prevalent comorbidity was DM, with radiological findings including fibroinfiltrates, consolidations, and cavities. CKD patients exhibited radiological features such as infiltrates, cavitations, and pleural effusion, while COPD patients presented with infiltrates and consolidations. Conclusion: The study provides valuable insights into the radiological manifestations of pulmonary TB and its comorbidities, offering a basis for improved management and treatment strategies for patients with pulmonary TB and comorbidities. Further research employing longitudinal designs and balanced representation of comorbid conditions is recommended to enhance the understanding of the interplay between TB and associated health conditions.